Persepsi Pelajar Terhadap Atribut Pekerjaan dan Implikasinya ke atas Pendidikan Universiti = Students' Perceptions on Employment Attributes and Their Implications on University Education (Universiti Kebangsaan Malaysia, 2007)
Globalisation and the advacement in ICT has intensified the demand for quality workforce. Today, employers no longer perceive academic competence alone to be sufficient and began calling for higher education institutions to produce graduates with highly developed transferable skills. Such request gains more weight recently as latest statistics has shown that unemployment among graduates has risen steadily in this country. This paper discusses the perceptions of the final year students of Universiti Kebangsaan Malaysia (National University of Malaysia) on the importance of and their levels of competency in job attributes. This study covers both the students of the sciences and the arts streams. Besides that, the students’ overall level of satisfaction on their courses and their university experiences as a whole is also assessed. A total of 200 final year undergraduate students have been sampled using stratified sampling and the data obtained were processed using analysis of the mean, t-test and analysis of variance. Results of the analyses showed that students tend to rate the importance of the skills more highly than their own ability and there are differences on levels of competency between gender, types of stream, GPA and ethnic groups. On the whole students tend to be satisfied with their programmes of studies and the university, and with the level of preparation for their future careers. However, the results show that some aspects need immediate attention particularly support and guidance from the academic staff and the university in terms of student’s career planning and the improvement of the facilities provided.